2020
DOI: 10.1007/s00345-020-03414-6
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol-based hydrogel rectal spacers for prostate brachytherapy: a systematic review with a focus on technique

Abstract: Introduction Radiation dose to the rectum in prostate brachytherapy (PBT) can be reduced by the use of polyethylene glycol (PEG) hydrogel spacers. This reduces the rate of rectal toxicity and allows dose escalation to the prostate. Our objectives were to provide an overview of technique for injection of a PEG hydrogel spacer, reduction in rectal dosimetry, gastrointestinal toxicity and potential complications. Methods We systematically reviewed the role of PEG hydrogel spacers in PBT using the Cochrane and PRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
0
22
0
4
Order By: Relevance
“…polyethylene glycol (PEG)] into the perirectal fat. Indeed, the use of spacers is associated with less rectal AEs ( 9 11 ). By way of an example, 222 patients with stage T1 or T2 prostate cancer and undergoing image-guided IMRT (79.2 Gy in 1.8-Gy fractions) were randomized to spacer implantation or no implantation ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…polyethylene glycol (PEG)] into the perirectal fat. Indeed, the use of spacers is associated with less rectal AEs ( 9 11 ). By way of an example, 222 patients with stage T1 or T2 prostate cancer and undergoing image-guided IMRT (79.2 Gy in 1.8-Gy fractions) were randomized to spacer implantation or no implantation ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the phase III study, almost all investigators rated the injection of SpaceOAR as easy or very easy, so this would not be expected as a barrier to more widespread use 15 . Additionally, studies have shown that acute rectal toxicity associated with hydrogel spacers is very uncommon (<2% of patients), 22 although patients may experience rectal discomfort prior to spacer hydrolysis 17,23 …”
Section: Discussionmentioning
confidence: 99%
“…(<2% of patients), 22 although patients may experience rectal discomfort prior to spacer hydrolysis. 17,23 The other major subgroup where the uro-oncologists would currently consider rectal spacers were those with pre-existing bowel conditions or those considered to be at higher risk of bowel toxicity. It is known that individuals with prostate cancer and inflammatory bowel disease experience an increased rate of adverse effects of radiotherapy, in particular EBRT, although to a lesser extent with brachytherapy.…”
Section: What's Newmentioning
confidence: 99%
“…Secondly, a misplaced injection can increase the chance of infection, inflammation, and rectal wall infiltration. Further, rectal ulcer and wall erosion, prostatic abscess and sepsis, recto‐urethral fistula, and purulent perineal drainage were reported in some cases, 16–18 whereas another study showed that the mislocated spacer decreases the level of rectal dose reduction 19 . Finally, although the injection of more hydrogel, and therefore, more separation is appealing from the dosimetric viewpoint, it is associated with a higher chance of procedure failure.…”
Section: Introductionmentioning
confidence: 99%